Montage of a dream the art and life of Langston Hughes - Tidwell, John Edgar; Ragar, Cheryl R. (University of Missouri Press, 2007)
"Contributors reexamine the continuing relevance of Langston Hughes's work and life to American, African American, and diasporic literatures and cultures. Includes fresh perspectives on the often overlooked "Luani of the Jungles," Black Magic, and works for children, as well as Hughes's more familiar fiction, poetry, essays, dramas, and other writings"--Provided by publisher.